Composition and antioxidant, antibacterial, and anti-HepG2 cell activities of polyphenols from seed coat of Amygdalus pedunculata Pall. (1st November 2018) - Lu, Cairui; Li, Cong; Chen, Bang; Shen, Yehua
Highlights: Thirty two polyphenolic compounds have been identified from Amygdalus pedunculata Pall seed coat. The characterization of the polyphenols indicated that it possessed high antioxidant activity. The results of bacteriostatic test showed that polyphenols had good antibacterial activity. HepG2 cell viability assays illustrated that polyphenols significantly inhibited cell proliferation while induced cell apoptosis. Abstract: This study aims at identifying the composition of polyphenols present in Amygdalus pedunculata Pall seed coat (APSC), and characterizing their antioxidant, antibacterial, and anticancer activities. The polyphenols from APSC were composed of 32 compounds. The compounds with important biological activities included apigenin 7- O -glucoside (the main component; 34.53 mg/100 g), quercitrin (23.43 mg/100 g), kaempferol (10.28 mg/100 g), naringenin (6.27 mg/100 g), cyanidin 3-rutinoside (5.76 mg/100 g), cyanidin 3- O -galactoside (5.19 mg/100 g), and quercetin (2.50 mg/100 g), as well as a variety of phenolic acids (gentisic acid, 23.13 mg/100 g; salicylic acid, 18.79 mg/100 g; gallic acid, 2.55 mg/100 g; etc.). Characterization of the identified polyphenols indicated that APSC possessed high antioxidant activity, due to its ability to reduce Fe 3+ and scavenge ABTS, DPPH, OH, O2 −, and H2 O2 free radicals. The ability of APSC to reduce Fe 3+ and scavenge ABTS radical, and H2 O2 was stronger than that of control group ascorbic acid (Vc). The data from bacteriostatic test showed that polyphenols from APSC had good antibacterial activity against Escherichia coli, Staphylococcus aureus, Bacillus cereus, and Bacillus subtilis, but showed no activity against Aspergillus niger. Cell viability assays using HepG2 cell illustrated that polyphenols from APSC significantly inhibited cell proliferation and induced cell apoptosis. The findings demonstrate that polyphenols from APSC may be utilized as is or further developed into natural antioxidant, antibacterial, and anticancer agents. This work also provides a basis for the development and utilization of Amygdalus pedunculata Pall.